1975
DOI: 10.1080/00223980.1975.9923947
|View full text |Cite
|
Sign up to set email alerts
|

Racial Prejudice, Belief Similarity, and Human Aggression

Abstract: Out of 66 undergraduates administered a scale designed to measure racial prejudice, 16 male Caucasians scoring above the median and 16 male Caucasians scoring below the median later interacted in a competition situation with an attitudinally similar or an attitudinally dissimilar black stimulus person. The competition situation was such that the Ss had the opportunity to aggress against their opponent using electric shock. The results indicated that highly prejudiced attitudes were related to high aggression s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
(2 reference statements)
0
8
0
Order By: Relevance
“…As with the majority of research within the intergroup domain, the attitudebehavior relationship in this context has focused almost exclusively on the link between negative attitudes and behaviors. For instance, there is a wealth of research demonstrating that negative out-group attitudes in adults and children, such as prejudice, are associated with negative intergroup behaviors including aggression or violence (Genthner, Shuntich, & Bunting, 1975;Van Zomeren, Fischer, & Spears, 2007). A new line of thinking has proposed that the decision to engage in negative or positive behaviors may develop through different processes (Aboud, 2003).…”
Section: Attitudes To Actionmentioning
confidence: 99%
“…As with the majority of research within the intergroup domain, the attitudebehavior relationship in this context has focused almost exclusively on the link between negative attitudes and behaviors. For instance, there is a wealth of research demonstrating that negative out-group attitudes in adults and children, such as prejudice, are associated with negative intergroup behaviors including aggression or violence (Genthner, Shuntich, & Bunting, 1975;Van Zomeren, Fischer, & Spears, 2007). A new line of thinking has proposed that the decision to engage in negative or positive behaviors may develop through different processes (Aboud, 2003).…”
Section: Attitudes To Actionmentioning
confidence: 99%
“…However, this assumption is sometimes contradicted. For instance, Genthner, Shuntich and Bunting (1975) found that highly prejudiced white subjects were more aggressive towards a black with similar beliefs than towards a black with dissimilar beliefs. The current study seeks to clarify some of the conditions that determine whether similarity improves or damages intergroup relations.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, despite holding a favourable view of another, a person may choose not to offer assistance if it comes at a cost to themselves or others (Batson, 2011). In addition, whereas intergroup research has historically focused on negative outgroup attitudes (e.g., prejudice and discrimination) linked with negative outgroup behaviours (e.g., aggression or violence; see Genthner, Shuntich, & Bunting, 1975;Genthner & Taylor, 1973;Van Zomeren, Fischer, & Spears, 2007), more recent studies examine positive pathways. Taylor et al (2014), for instance, found that positive outgroup attitudes were associated with selfreported outgroup prosocial behaviour over time among young people in a postaccord society.…”
Section: Attitudes To Actionmentioning
confidence: 99%